2021
DOI: 10.1002/oby.23246
|View full text |Cite
|
Sign up to set email alerts
|

Dietary weight loss in people with severe obesity stabilizes neuropathy and improves symptomatology

Abstract: ObjectiveThe aim of this study was to determine the effect of dietary weight loss on neuropathy outcomes in people with severe obesity.MethodsA prospective cohort study of participants attending a medical weight‐management program was followed. Weight loss was achieved with meal replacement of 800 kcal/d for 12 weeks and then transitioning to 1,200 to 1,500 kcal/d. The coprimary outcomes were changes in intraepidermal nerve fiber density (IENFD) at the distal leg and proximal thigh. Secondary outcomes included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
(32 reference statements)
1
9
1
Order By: Relevance
“…While bariatric surgery is one potential intervention to simultaneously improve multiple metabolic risk factors, another comparable intervention is medical weight loss. We previously studied PN and CAN outcomes in 72 participants with obesity 2 years after medical weight loss using a similar study design [21]. We found that medical weight loss (MWL) more modestly improved the metabolic profile compared with bariatric surgery, with 10.3% weight loss for MWL vs 23.8% for bariatric surgery, a reduction in the National Cholesterol Education Program (NCEP)-defined waist circumference of 7.3% for MWL vs 12.5% for bariatric surgery, a reduction in triacylglycerol of 17.7% for MWL vs 19.1% bariatric surgery, increases in HDL-cholesterol of 11.5% for MWL vs 38.6% for bariatric surgery, and a reduction in HbA 1c of 5.0% for MWL vs 7.5% for bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While bariatric surgery is one potential intervention to simultaneously improve multiple metabolic risk factors, another comparable intervention is medical weight loss. We previously studied PN and CAN outcomes in 72 participants with obesity 2 years after medical weight loss using a similar study design [21]. We found that medical weight loss (MWL) more modestly improved the metabolic profile compared with bariatric surgery, with 10.3% weight loss for MWL vs 23.8% for bariatric surgery, a reduction in the National Cholesterol Education Program (NCEP)-defined waist circumference of 7.3% for MWL vs 12.5% for bariatric surgery, a reduction in triacylglycerol of 17.7% for MWL vs 19.1% bariatric surgery, increases in HDL-cholesterol of 11.5% for MWL vs 38.6% for bariatric surgery, and a reduction in HbA 1c of 5.0% for MWL vs 7.5% for bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary PN outcomes included nine nerve conduction study measures of three nerves (peroneal distal motor latency, peroneal amplitude, peroneal F wave index, peroneal CV, sural peak latency, sural amplitude, tibial distal motor latency, tibial amplitude, tibial F wave index), the Michigan Neuropathy Screening Instrument (MNSI) questionnaire, examination and combined index [17], the Utah Early Neuropathy Scale (UENS) [18], quantitative sensory testing (QST) of vibration and cold detection thresholds, vibration perception threshold from neurothesiometer testing [19] and monofilament testing. The nerve conduction studies, QST, neurothesiometer and monofilament testing were completed as previously described [19][20][21]. We defined clinical PN using the Toronto Consensus Definition of probable neuropathy as determined by one of six neuromuscular specialists (including BCC); this required the presence of at least two neuropathy symptoms, abnormal sensory examination or abnormal reflexes [22].…”
Section: Pn Outcomesmentioning
confidence: 99%
“…The prevalence of peripheral neuropathy measured with the Michigan Neuropathy Screening Instrument (MNSI) was found to be reduced (pre-bariatric surgery 20.4% to post-bariatric surgery 10.5%) approximately 10 years after Roux-en-Y gastric bypass and sleeve gastrectomy [47]. Several randomized controlled studies (DiRECT, DROPLET and PREVIEW) have demonstrated the efficacy of low-calorie diets (LCDs; 800-850 kcal/day) in severe obesity [48][49][50]; and recently, a dietary weight loss study of 800 kcal/day (for 12 weeks) followed by 1200-1500 kcal/day resulted in an improvement in metabolic parameters, whilst intraepidermal nerve fibre density (IENFD) remained stable after 2 years [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, in both studies, measures of large fibre function and nerve conduction did not improve [ 79 , 80 ]. Another prospective study of participants attending a medical weight management program showed an improvement in symptomology and a stability of intraepidermal nerve fibre density over 2 years [ 81 ]. Taken together, these findings suggest that improvements in metabolic profiles, as may occur in the setting of bariatric surgery or caloric restriction-induced weight loss, may be associated with improvements in small fibre measures and neuropathy symptom scores.…”
Section: Metabolic Peripheral Neuropathymentioning
confidence: 99%